DETECTION OF AMINOGLYCOSIDE AND QUINOLONE RESISTANCE GENES AND EVALUATION OF POLYMYXIN B SUSCEPTIBILITY PROFILE IN ACINETOBACTER BAUMANNII CLINICAL ISOLATES IN TEHRAN, IRAN DURING 2015-2016 - Mohsen Heidary (Mediterranean Journal of Hematology and Infectious Diseases)
ABSTRACT